(−)-Epigallocatechin gallate protected molecular structure of collagen fibers in sea cucumber Apostichopus japonicus body wall during thermal treatment. (April 2020) - Dong, Xiufang; Shen, Ping; Yu, Meiqi; Yu, Chenxu; Zhu, Beiwei; Qi, Hang
Abstract: During thermal tenderization of sea cucumber body wall, protein oxidation always happens which disrupts its structural integrity. In this study, we investigated the effects of (̶̶−)-epigallocatechin gallate (EGCG, at 0, 5, 50, 125, 250 μg/mL) to protect the structure of heated collagen fibers (CFs) in sea cucumber Apostichopus japonicus body wall. Many disintegrated collagen fibrils and fibril bundles were observed in samples with no EGCG by scanning electron microscope, while the integrity of CFs was protected in samples with 125 μg/mL EGCG. Electron paramagnetic resonance results indicated heat-induced OH in heated CFs were neutralized by EGCG, up to 83% in samples with 250 μg/mL EGCG. Chemical analysis of the soluble fragments in heated CFs showed plenty of proteins and glycosaminoglycan were released in heated CFs, and the addition of EGCG into the samples reduced their dissolution. Analysis of differential scanning calorimetry and thermogravimetry indicated EGCG could enhanced the thermostability of CFs. Fourier transform infrared spectroscopy results showed EGCG at 125 μg/mL prevented the conversion of α-helixes to β-sheets, and affected N–H bending coupled with C–N stretching. In conclusion, EGCG could protect the structure of CFs in a dosage dependent way, and 125 μg/mL was the most effective. Graphical abstract: Image 1 Highlights: Heating caused CFs depolymerization and dissolution of protein and glycosaminoglycan. Thermal treatment reduced thermostability and secondary structural stability of CFs. EGCG protected the structure of CFs in a dosage dependent way. EGCG played anti-oxidation roles by scavenging free radical to protect CFs. EGCG promoted protein aggregation affecting hydrogen bond, not covalent bonds.